2006
DOI: 10.1111/j.1365-2648.2006.04012.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses, interventions and outcomes – application and impact on nursing practice: systematic review

Abstract: Despite variable results, the trend indicated that nursing diagnostics improved assessment documentation, the quality of interventions reported, and outcomes attained. The study reveals deficits in reporting of signs/symptoms and aetiology. Consequently, staff educational measures to enhance diagnostic accuracy are recommended. The relationships among diagnoses, interventions and outcomes require further evaluation. Studies are needed to determine the relationship between the quality of documentation and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
0
23

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(202 citation statements)
references
References 39 publications
10
169
0
23
Order By: Relevance
“…In some diagnoses, there was a confusion and a change between the defining characteristic and the related factor, leading to a constant concern. Corroborating with the results of the present study, a systematic review showed that there is a difficult in the process to prepare nursing diagnoses concerning the capacity to associate them with signs, symptoms and etiology that characterize and determine that diagnosis (9) .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In some diagnoses, there was a confusion and a change between the defining characteristic and the related factor, leading to a constant concern. Corroborating with the results of the present study, a systematic review showed that there is a difficult in the process to prepare nursing diagnoses concerning the capacity to associate them with signs, symptoms and etiology that characterize and determine that diagnosis (9) .…”
Section: Discussionsupporting
confidence: 78%
“…Record analysis of nursing diagnoses in the charts can contribute to identify permanent education needs, as well as to estimate the participation of nurses in the outcomes reached by patients (9) and to generate useful data to the management and administration sectors (10) . It is also relevant to the identification of specific diagnoses of a certain unit and because of that it will enhance the process of preparing diagnoses, improving their accuracy and, above all, contributing to the planning of more accurate and adequate interventions to the profile of the clientele cared for (11) .…”
Section: Introductionmentioning
confidence: 99%
“…The literature related to nursing diagnoses, the validation of data collection instruments, the evaluation of the trauma patient and the evaluation of the critical patient in an emergency situation defined the model (construction) of the data collection instrument (10)(11)(12)(13) . The NANDA2009-11 was used as a guide for selecting the diagnoses (5) .…”
Section: Methodsmentioning
confidence: 99%
“…Despite a certain degree of consensus about the fact that the nursing process can contribute to a more autonomous and evidence-based practice, in nursing, few institutions actually adopt all of its steps (11) . To underline the importance of the nursing process, a systemic review carried out in 2007 identified 14 studies that proved the better quality of nursing documentation/assessments when the nursing diagnosis was applied (12) . The systemization of the nursing process supports the development of interdisciplinary and humanized care methodologies, serving as a work process.…”
Section: Iabp-related Complicationsmentioning
confidence: 99%